Sleep disturbances and dementia. Issue 1 (16th December 2014) - Cipriani, Gabriele; Lucetti, Claudio; Danti, Sabrina; Nuti, Angelo
Abstract Sleep is a complex behavioural state, the ultimate functions of which remain poorly understood. It becomes more fragmented as we age, with more night‐time awakenings and greater tendency for daytime sleep. The magnitude of disordered sleep among individuals affected by dementia has been clearly demonstrated, and disturbed sleep is a major clinical problem in dementia. Comorbid insomnia and other sleep disturbances are common in patients with neurodegenerative disorders, such Alzheimer's disease and other dementing disorders. How and when sleep problems manifest themselves can depend on the type of dementia involved as well as the stage of the dementia. However, differences in sleep pattern presentation show more variation during the initial stages of dementias than they do during the later stages. Effective, pragmatic interventions are largely anecdotal and untested.